O saber pedagógico feminista das mulheres praticantes de yoga no movimento Hare Krishna - Uma pedagogia Vaishnavi de consciência, luta e coletividade - Santos, Otávio Augusto Chaves Rubino dos (2023)
The present thesis entitled “The knowledge of the women who practice yoga in the Hare Krishna movement - a Vaishnavi pedagogy of conscience, fight and collectivity” and defended in the Graduate Program in Education at the Federal University of Paraíba (PPGE - UFPB) - in the line of research of Cultural Studies of Education (ECE) - is structured from the concept of knowledge, having, in this, the key idea followed in the research. The object of investigation refers to the Vaishnavi feminist pedagogical knowledge in the Hare Krishna movement”. In summary, the term Vaishnavi refers to women who practice yoga. The thesis defended is that the Vaishnavis knowledge in the Hare Krishna movement presents a feminist pedagogical singularity that transforms unequal gender relations. The general objective was to analyze and describe the discourse order of the feminist pedagogical knowledge of the Vaishnavis of the Hare Krishna movement. The theoretical-methodological approach is Archaeological Analysis of the Discourse (AAD), an approach by which Foucault gives us, in his first works, the basic conditions for researching from archaeological analysis of the discourse perspective. I research the Vaishnavis knowledge from the specificities of AAD. It is research on what can be said, or the interdict itself, by these women in a certain order of discourse. As final considerations, I can say that I showed that there is a Vaishnavi pedagogy that has its own singularities such as awareness, struggle and collectivity. It is knowledge that trigger enunciations related to community issues, reciprocal empowerment, building bridges and communities of love, heart-to-heart relationships that connect common hopes. This pedagogy is formed by a collective of knowledge. These new concepts are the main findings of this research. In conclusion, I emphasize that there are, in this thesis, two types of research results. The first refers to the findings from the analysis and description of the sources. The second is the finding from the point of view of archeology theory: a reflection on archeology as a way of life (archeology of living).